Effects of Interleukin-17A on Osteogenic Differentiation of Isolated Human Mesenchymal Stem Cells - Osta, Bilal; Lavocat, Fabien; Eljaafari, Assia; Miossec, Pierre (Frontiers in Immunology, 2014)
OBJECTIVES: Rheumatoid arthritis (RA) is characterized by defective bone repair and excessive destruction, and ankylosing spondylitis (AS) by increased ectopic bone formation with syndesmophytes. Since TNF-α and IL-17A are involved in both diseases, this study investigated their effects on the osteogenic differentiation of isolated human bone marrow derived mesenchymal stem cells (hMSCs). METHODS: Differentiation of hMSCs into osteoblasts was induced in the presence or absence of IL-17A and/or TNF-α. Matrix mineralization (MM) was evaluated by alizarin red staining and alkaline phosphatase activity (ALP). mRNA expression was measured by qRT-PCR for BMP2 and Runx2, genes associated with osteogenesis, of DKK1, a negative regulator of osteogenesis, of Schnurri-3 and RANKL, associated with the cross talk with osteoclasts, and of TNFRI and TNFRII. RESULTS: TNF-α alone increased both MM and ALP activity. IL-17A alone increased ALP but not MM. Their combination was more potent. TNF-α alone increased BMP2 mRNA expression at 6 and 12 hr. These levels decreased in combination with IL-17A at 6 hr only. DKK1mRNA expression was inhibited by TNF-α and IL-17A either alone or combined. Supporting an imbalance towards osteoblastogenesis, RANKL expression was inhibited by TNF-α and IL-17A. However, TNF-α but not IL-17 alone decreased Runx2 mRNA expression at 6 hr. In parallel, TNF-α but not IL-17 alone increased Schnurri-3 expression with a synergistic effect with their combination. This may be related to an increase of TNFRII overexpression. CONCLUSION: IL-17 increased the effects of TNF-α on bone matrix formation by hMSCs. However, IL-17 decreased the TNF-α -induced BMP2 inhibition. Synergistic interactions between TNF-α and IL-17 were seen for RANKL inhibition and Schnurri-3 induction. Such increase of Schnurri-3 may in turn activate osteoclasts leading to bone destruction as in RA. Conversely, in the absence of osteoclasts, this could promote ectopic bone formation as in AS